2022
DOI: 10.3390/ijerph191912227
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine in Inherited Metabolic Disorders Patients: A Cross-Sectional Study on Rate of Acceptance, Safety Profile and Effect on Disease

Abstract: Background: Vaccines for COVID-19 have had a significant impact on the spread of COVID-19 infection, reducing the incidence and mortality of the infection in several countries. However, hesitancy toward this vaccine is a global health issue for the general population The Vaccine acceptance rate among patients affected with inherited metabolic disorders (IMD), as well as safety profile, has not been described. Methods: We conducted a cross-sectional study, based on a telephone survey, investigating the COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Of those who contracted the disease, 37% reported "long Covid" symptoms, the most frequent of which were shortness of breath, palpitations and fever, with an average duration of 81 (± 74) days. Tummolo et al recently published an interesting study evaluating 174 patients; they reported that before October 2021, 94% of the patients had received at least one dose of vaccine; unvaccinated patients were 27.1 years old on average [17]. The two main reasons were fear of the vaccine being intrinsically dangerous and fear that getting vaccinated could worsen their IMD.…”
Section: Discussionmentioning
confidence: 99%
“…Of those who contracted the disease, 37% reported "long Covid" symptoms, the most frequent of which were shortness of breath, palpitations and fever, with an average duration of 81 (± 74) days. Tummolo et al recently published an interesting study evaluating 174 patients; they reported that before October 2021, 94% of the patients had received at least one dose of vaccine; unvaccinated patients were 27.1 years old on average [17]. The two main reasons were fear of the vaccine being intrinsically dangerous and fear that getting vaccinated could worsen their IMD.…”
Section: Discussionmentioning
confidence: 99%
“…Tummolo et al recently published an interesting study evaluating 174 patients; they reported that before October 2021, 94% of the patients had received at least one dose of vaccine; unvaccinated patients were 27.1 years old on average [17]. The two main reasons were fear of the vaccine being intrinsically dangerous and fear that getting vaccinated could worsen their IMD.…”
Section: Discussionmentioning
confidence: 99%